Semi-Markov Risk Models for Finance, Insurance and Reliability - Janssen, Jacques; Manca, Raimondo (Springer US : Imprint: Springer, 2007)
This book presents applications of semi-Markov processes in finance, insurance and reliability, using real-life problems as examples. After a presentation of the main probabilistic tools necessary for understanding of the book, the authors show how to apply semi-Markov processes in finance, starting from the axiomatic definition and continuing eventually to the most advanced financial tools, particularly in insurance and in risk-and-ruin theories. Also considered are reliability problems that interact with credit risk theory in finance. The unique approach of this book is to solve finance and insurance problems with semi-Markov models in a complete way and furthermore present real-life applications of semi-Markov processes. Audience This book is intended for applied mathematicians, statisticians, financial intermediaries, actuaries, engineers, operations researchers.